A 1-Month-Old Baby with Osteogenesis Imperfecta: A Case Report - Juliansen, Andry; Meilyn, Anne; Tampake, Lisa Rehinda (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Osteogenesis imperfecta (OI) is a connective tissue formation disorder that is generally characterized by bone fragility, osteopenia, blue sclera, dentinogenesis imperfecta (DI), and hearing loss. This disease occurs due to changes in collagen type 1 that form the basis of bone formation so that bones tend to be thinner and smaller. The bones become weak and easily cracked. OI has been classified by type according to the system based on the mode of inheritance, clinical features, and information from the X-ray. There are four types of osteogenesis imperfecta, namely Type I, Type II, Type III, and Type IV. Health problems are often seen in children and adults who have OI include: short stature, weak tissues, fragile skin, muscle weakness, and loose joints, bleeding, easy bruising, frequent nosebleeds, and tiny amounts of heavy bleeding from the wound, impaired loss of hearing can begin in childhood and affects approximately 50 % of adults, breathing problems, a higher incidence of asthma plus risk for other lung problems, spinal curvature.